Are Infographics Worth It?: An Assessment of Information Retention in Relation to Information Embedded in Infographics. (2nd October 2022) - Abbazio, Jessica M.; Yang, Zoua Sylvia
ABSTRACT: Infographics are an effective means to communicate with audiences, draw attention, and make concepts digestible in a quick and straightforward way. This study explores students' opinions on infographics used in library instruction, and provides quantitative data to help librarians determine whether these tools will help students engage with text and retain key concepts. Based on research conducted with undergraduate music students at two universities, DePauw University and the University of Minnesota, Twin Cities, this paper examines how students understand and interact with content embedded in infographics, and measures retention of information presented in either plain-text or infographic form.